2013
DOI: 10.1016/j.nbd.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Increased anandamide uptake by sensory neurons contributes to hyperalgesia in a model of cancer pain

Abstract: Opioids do not effectively manage pain in many patients with advanced cancer. Because anandamide (AEA) activation of cannabinoid type-1 receptors (CB1R) on nociceptors reduces nociception, manipulation of AEA metabolism in the periphery may be an effective alternative or adjuvant therapy in the management of cancer pain. AEA is hydrolyzed by the intracellular enzyme fatty acid amide hydrolase (FAAH), and this enzyme activity contributes to uptake of AEA into neurons and to reduction of AEA available to activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Moreover, growth of painful bone tumors is associated with enhanced FAAH expression in the paw bearing the tumor and the DRG innervating it 24 . This effect – along with a parallel, but independent increase in carrier-mediated anandamide uptake by neurons and/or other cells of the DRG 56 – may be responsible for the observed deficit in anandamide mobilization 52 .…”
Section: Endogenous Cannabinoids: Antinociceptive Response To Injurymentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, growth of painful bone tumors is associated with enhanced FAAH expression in the paw bearing the tumor and the DRG innervating it 24 . This effect – along with a parallel, but independent increase in carrier-mediated anandamide uptake by neurons and/or other cells of the DRG 56 – may be responsible for the observed deficit in anandamide mobilization 52 .…”
Section: Endogenous Cannabinoids: Antinociceptive Response To Injurymentioning
confidence: 92%
“…Experiments with Raw264.7 macrophages suggest that the PLC/phosphatase pathway mediates the initial spike in anandamide production 29 (Figure 3), whereas the delayed decline in OEA and PEA results from a down-regulation in NAPE-PLD transcription due to reduced acetylation of histone proteins bound to the NAPE-PLD promoter 84 . The ability of tissue damage to suppress FAE mobilization has been documented using multiple animal models of inflammation and peripheral neuropathy 53,56,70,83 . Adding clinical relevance to these observations, one study found that the concentrations of OEA and PEA in synovial fluid are lower in subjects with rheumatoid arthritis and osteoarthritis than in healthy controls 85 .…”
Section: Endogenous Ppar-α Agonists: Homeostatic Control Of Nociceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…During extraction of lipids, 5 pmol of deuterated ( d) 8 -AEA and 100 pmol of d 8 -2-AG and d 8 -palmitoylethanolamine (PEA, Cayman Chemical, Ann Arbor, Michigan) were added as internal standards. PEA is included in this report because it is another fatty acid ethanolamide that modulates transduction of noxious stimuli [32]. The total lipid weight was determined by weighing the vials containing the dried organic phases of each sample.…”
Section: Methodsmentioning
confidence: 99%
“…An additional actor of the endocannabinoid system includes the anandamide membrane transporter (AMT) which displays a key role in modulating anandamide's biological functions (Chicca et al, 2012;Fowler, 2013;Khasabova et al, 2013;Leung et al, 2013;Nicolussi and Gertsch, 2015). The available evidence indicates that injections of blocker of AMT known as VDM-11 promote sleep in rats (Murillo-Rodrı´guez et al, 2008.…”
Section: Introductionmentioning
confidence: 99%